Dependence of the Electrochemical Behavior of Redox-Functionalized Calix[4]arene Monolayers on Intermolecular Interactions in a Structurally Controlled Interfacial Architecture - Silva-Molina, C; Silva-Molina, C; Candia-Candia, C; Candia-Candia, C (American Chemical Society, 2026)
The selective surface modification and functionalization methods through organic or inorganic grafting are a permanent challenge for constructing custom-made molecular interfaces with high structural control as part of the electroactive surfaces. This work presents calix[4]arene derivatives as surface modification agents to control the interface architecture through molecular design. This strategy corresponds to the use of diazo calix[4]arene derivatives, with the lower rim functionalized with ferrocene terminal groups, to control the coverage and spatial arrangement of an electroactive monolayer covalently attached to a glassy carbon (GC) electrode surface toward modulation of interfacial electron transfer. The location of ferrocene terminal groups on the lower rim of calix[4]arene derivatives, distal vs proximal, tunes the intermolecular interactions of ferrocene units, modulating the interfacial electrochemical behavior of these systems. The electrochemical results and computational studies showed that the covalent immobilization of the ferrocene-calix[4]arene derivatives on the GC electrode increases the molecular rigidity and the intermolecular interactions of the ferrocene terminals, unlike what was observed in solution. This effect is more significant in the graft based on the proximal ferrocene-calix[4]arene derivative, which showed a much higher nonideal voltammetric behavior in its electrochemical response.